Legal Protection and Notary Responsibilities: A Review of the Deed of Testament in the Context of Civil Cases - Robiatul Adawiyah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
A testament deed is an authentic deed that has perfect proof. Testament is a unilateral will, so it does not require agreement with other parties, as a partij deed, the Notary only formulates the wishes of the Testator, because it involves property it often causes problems so that it is possible for a lawsuit against the testament deed. Analysing the decision of the Yogyakarta District Court No. 58/PDT.G/2011/PN.YK.Problem formulation: Legal protection for Notary related to the deed of will in civil case connected with Law No. 2 Year 2014, and Notary's responsibility towards the deed of will in civil case. The purpose of the research: to know the legal protection for Notary related to the deed of will in civil case in relation with Law No. 2 Year 2014. To find out the responsibilities of the Notary towards the testamentary deed in civil cases. The research method used in this research uses a normative juridical approach with additional interviews. The normative juridical approach is sourced from data collection obtained from library materials and then analysed by qualitative analysis method. The conclusion of the research is that the Notary is only responsible for the formal form of the deed he made, and is not responsible for the content of the deed. The protection of the Notary is that the will deed is a unilateral act, does not need the consent of other parties, as a partij deed, the Notary only formulates the wishes of the Testator, not as a party to the deed (Articles 52, 53 UUJN), besides that it is based on Article 66 of the UUJN which previously had to be approved by the MPD, currently replaced by the Notary Honor Council. Notaries are protected if they have fulfilled the requirements that must be met in making a deed of will. The author suggests that in making a deed, it is necessary to be careful, and adhere to the rules of the Notary Office. In addition, the Notary needs to provide information related to the will deed to the maker of the will and the party concerned. The government is expected to form regulations governing the protection of Notaries.